2019
DOI: 10.1039/c9gc00690g
|View full text |Cite
|
Sign up to set email alerts
|

Chromium(iii) in deep eutectic solvents: towards a sustainable chromium(vi)-free steel plating process

Abstract: A sustainable Cr(iii) electrolyte was brought one step closer to industrial application by in-depth understanding of the (coordination) chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…L e (6) where q m (mg/g) is the maximum adsorption concentration of Cr(VI), q e (mg/g) is the adsorption capacity, C e (mg/L) is the equilibrium concentration of Cr(VI), and K L (L/mg) is the equilibrium constant associated to adsorption energy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…L e (6) where q m (mg/g) is the maximum adsorption concentration of Cr(VI), q e (mg/g) is the adsorption capacity, C e (mg/L) is the equilibrium concentration of Cr(VI), and K L (L/mg) is the equilibrium constant associated to adsorption energy.…”
Section: Resultsmentioning
confidence: 99%
“…The handling of heavy metals in water has gained intense scrutiny in recent decades. As a common difficult-to-remove toxic heavy metal pollutant, chromium ions are not only liable for infamous environmental hazards but also cause serious harm to human health. Chromium has two oxidation states, Cr­(III) and Cr­(VI), and the latter is considered to be more dangerous as a carcinogen . By contrast, Cr­(III) is less portable in the ecosystem and thus not much toxic to organisms .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, chromium electrodeposition from ionic liquids (ILs) and deep eutectic solvents (DES) has also been reported [20][21][22]. It was thought that by using these non-aqueous media some of the abovementioned obstacles would be overcome, but issues regarding the industrial application of these technologies, which require dedicated plants and careful wastes management, remain.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the use of MS for the deposition of Cr-based coatings, such as Cr-alloys and CrN, for industrial and technological applications, has been already reported [32,33]. Nevertheless, comparative studies on the morphological and structural characteristics of layers derived from MS and electrochemical deposition methods are rather scarce in the literature [20][21][22]. Although the pros and cons of the two different deposition methods are well known, specific considerations may apply to the particular system under investigation, impairing the straightforward generalization of their characteristics such as color, roughness, type of defects, and corrosion behavior [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…with Ni and composite Ni plating, 2-5 Zn 6 and Zn alloy plating 7 and especially Cr(III) plating. 8,9 Besides, it can be clearly seen in scientic literature that research is oen directed towards surface nishing of specic construction materials such as stainless steels and light metalstitanium and aluminum alloys. For these materials, the emphasis is on the use of DES-based baths mostly for two different processes: anodizing or electropolishing.…”
Section: Introductionmentioning
confidence: 99%